Street Vended Food in Developing World: Hazard Analyses - Rane, Sharmila (Springer-Verlag, 2011)
Street food vending has become an important public health issue and a great concern to everybody. This is due to widespread food borne diseases, due to the mushrooming of wayside food vendors who lack an adequate understanding of the basic food safety issues. Major sources contributing to microbial contamination are the place of preparation, utensils for cooking and serving, raw materials, time and temperature abuse of cooked foods and the personal hygiene of vendors. Various studies have identified the sources of food safety issues involved in street foods to be microorganism belonging to the genus Bacillus, Staphylococcus, Clostridium, Vibrio, Campylobacter, Listeria, Salmonella. Application of sound risk analysis policies is being advocated to provide a scientific base to the host of risk management option which India may need to explore to ensure public health and safety.